2016
DOI: 10.3847/2041-8205/822/1/l20
|View full text |Cite
|
Sign up to set email alerts
|

Velocity-Resolved Hot Water Emission Detected Toward Hl Tau With the Submillimeter Array

Abstract: Using the Submillimeter Array (SMA) on Mauna Kea, the H O 2 16 10 2,9 -9 3,6 transition (E up =1863 K) at 321.2 GHz has been detected toward the embedded low-mass protostar HL Tau. The line centroid is blueshifted by 20 km s −1 with respect to the source velocity, and it has a FWHM of 25 km s −1 . The emission is tentatively resolved and extends ∼3″-4″ over the sky (∼2 beams), or ∼500 au at the distance of Taurus. The velocity offset, and to a lesser degree the spatial extent of the emission, show that the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Here we mention that the ortho-H 2 16 O 321 GHz line has been detected in the disk and outflow around the massive protostar candidate, Source I in Orion KL (Hirota et al 2014), using ALMA, and around the embedded low mass Class I protostar, HL Tau, using SMA (Kristensen et al 2016). The interstellar para-H 2 16 O 183 GHz and the para-H 2 18 O 203 GHz lines were detected for the first time in the Orion and DR21(OH) molecular clouds (e.g., Phillips et al 1978).…”
Section: Requirement For the Future Observationsmentioning
confidence: 93%
“…Here we mention that the ortho-H 2 16 O 321 GHz line has been detected in the disk and outflow around the massive protostar candidate, Source I in Orion KL (Hirota et al 2014), using ALMA, and around the embedded low mass Class I protostar, HL Tau, using SMA (Kristensen et al 2016). The interstellar para-H 2 16 O 183 GHz and the para-H 2 18 O 203 GHz lines were detected for the first time in the Orion and DR21(OH) molecular clouds (e.g., Phillips et al 1978).…”
Section: Requirement For the Future Observationsmentioning
confidence: 93%
“…Thus the possibility of a successful detection is expected to increase in such Herbig Ae disks and could be achieved with current ALMA capabilities. Here we mention that the 933.28 µm line has been detected with high spectral resolution in the disk and outflow around the massive protostar candidate, Source I in Orion KL (Hirota et al 2014), using ALMA, and around the embedded low mass protostar (Class I), HL Tau, using SMA (Kristensen et al 2016). Kristensen et al (2016) suggested that future observations at higher sensitivity and angular resolution with ALMA will clarify the origin of this water emission from HL Tau and resolve the disk structures.…”
Section: Previous H 2 O Line Observations In Herbig Ae Disksmentioning
confidence: 99%
“…The flux is much lower than the tentative detection by ref. 20 with the Submillimeter Array, where, however, the line is shifted by 30 km s −1 from the systemic velocity, indicating that the proposed emission may be originating from a largescale flow that we filter out in our highresolution data. For the 183 and 325 GHz lines, intensityweighted velocity maps were generated using the bettermoments package 44 after applying 4σ and 3σ clipping to individual channels, respectively.…”
Section: Methodsmentioning
confidence: 92%
“…19). In quiescent sources, except the candidate detections in the AS 205N and HL Tauri (HL Tau) disks, no detection of thermal emission at (submillimetre) wavelengths has been reported in the literature [20][21][22][23] .…”
Section: The Spatial Distribution Of Water Vapourmentioning
confidence: 99%